Analisis Komparasi Lokasi, Kualitas, dan Harga Terhadap Keputusan Pembelian (Studi Sentra PKL Bratang Binangun Surabaya dan Sentra PKL Bungkul Surabaya) - Amanullah, Natasya; Mulyati, Diana; Maruta, IGN Anom (Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe Center for Street Vendors (PKL) Bratang Binangun, this location can be said to be clean, the seller has an organized stand, consumers feel more relaxed to enjoy food. The quality of the food at the Bratang Binangu Street Vendor Center (PKL) is also well maintained so that consumers feel satisfied and the price is also the main requirement for customers to come, prices in the range of Rp. 3,000-Rp. 25,000 can already enjoy food at the Trade Center Street Vendor (PKL) Bratang Binangun. There is also the Bungkul Street Vendor Center (PKL) in Surabaya. The location is behind Taman Bungkul Surabaya, Taman Bungkul Surabaya is the center of Surabaya. This location has a lot of parking so it doesn't make it difficult for consumers to come. The quality of food at the Bungkul Street Vendor Center (PKL) in Surabaya sells so many kinds of East Java specialties. The prices offered from this place are also different, but again, looking at the Bungkul Street Vendor Center (PKL) in Surabaya, which stands in the center of the city, the price has increased slightly compared to other centers. Comparison of location to the Bratang Binangun and Bungkul PKL Centers Surabaya There is an insignificant difference from the location variable, the quality comparison to the Bratang Binangun and Bungkul PKL Centers is an insignificant difference from the quality variable, the price comparison to the Bratang Binangun and Bungkul PKL Centers In Surabaya there is an insignificant difference from the price variable, there is also a comparison of purchasing decisions at the Bratang Binangun and Bungkul PKL Centers in Surabaya, there is an insignificant comparison of the Purchase Decision variable.Keywords: Location, Quality, Price and Purchase Decision